IMPLEMENTASI LITERASI BAHASA BERBASIS PERMAINAN UNTUK SISWA KELAS RENDAH DI SDN 46 AMPENAN - Mar`atul Hayati; Nindia Wulandari; Nurhayati; Risky Nugraha Putra; Anisya; Baiq Freccilia Dwi Syara; Tini Apriatiningsih; Syafruddin Muhdar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to describe and analyze the implementation of game-based language literacy in improving the literacy skills of lower-grade students at SDN 46 Ampenan. The study addresses the issues of low reading interest, limited reading comprehension, and the dominance of conventional teacher-centered learning methods. Using a qualitative approach with a descriptive research type, data were collected through observation, in-depth interviews with teachers and students, and documentation. Data analysis followed the interactive model by Miles and Huberman, involving data reduction, data display, and conclusion drawing. The results indicate that game-based literacy, incorporating educational games into reading, writing, listening, and speaking activities, significantly increases student motivation and active participation. The integration of game elements creates a dynamic and enjoyable learning environment, allowing students to learn naturally through direct experience, which leads to a deeper and more meaningful understanding of literacy.